Kepala Negara Perempuan Dalam Perspektif Hadis - Najib, Agus Moh. (Musawa Jurnal Studi Gender dan Islam, 2004)
The classical ulama agreed that women are not allowed to be the head ofa state. This view was based on, among others, the context when they lived. Besides, there was an often quoted hadith stating that it was forbidden for the Muslim community to choose women as their head of state. This is of course a discriminative view, 'especially when is considered in light of current socio-political circumstances. This article is an initial attempt to scrutinize this very hadith both from its chain of transmission and from its content. There are two approaches Â developed by the ulama in understanding hadith texts: some tended to explore the generality of the hadith texts, and some tended to analyze the context within which the texts were written